2016
DOI: 10.3928/19404921-20160120-01
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Information on Post-Acute Care Services

Abstract: The purpose of this study was to explore what hospitalized patients would like to know about post-acute care (PAC) services to ultimately help them make an informed decision when offered PAC options. Thirty hospitalized adults 55 and older in a Northeastern U.S. academic medical center participated in a qualitative descriptive study with conventional content analysis as the analytical technique. Three themes emerged. Participants were interested in (1) receiving practical information about the services, (2) un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 30 publications
(42 reference statements)
3
26
0
Order By: Relevance
“…This is consistent with existing literature, which has found that home health case managers do not provide quality information or make recommendations but merely provide lists of agency names and contact information . It is also consistent with research that has highlighted the importance of providing information to patients because consumer understanding of postacute services is associated with decision‐making . In the present study, respondents reported feeling that medical staff were not allowed to offer guidance or recommendations, even though most nursing home admissions come from the hospital and hospital discharge planners are key stakeholders in the placement process.…”
Section: Discussionsupporting
confidence: 89%
“…This is consistent with existing literature, which has found that home health case managers do not provide quality information or make recommendations but merely provide lists of agency names and contact information . It is also consistent with research that has highlighted the importance of providing information to patients because consumer understanding of postacute services is associated with decision‐making . In the present study, respondents reported feeling that medical staff were not allowed to offer guidance or recommendations, even though most nursing home admissions come from the hospital and hospital discharge planners are key stakeholders in the placement process.…”
Section: Discussionsupporting
confidence: 89%
“…This study was approved by the University of Pennsylvania's Institutional Review Board. Other findings from the larger study are published elsewhere (7). …”
Section: Methodsmentioning
confidence: 62%
“…Presenting explanations of the professional services PAC encompasses such as medication reconciliation, continued monitoring of symptoms, teaching, care coordination, pain management, and wound care could improve acceptance of these valuable services. Informing patients and families about the specifics of potential services they might receive and how a particular service matches their needs, may provide important opportunities for making more informed decisions (7). Educational campaigns aimed at providers and patients and their family caregivers may benefit the PAC industry by highlighting positive aspects, dispelling negative stereotypes, and managing expectations as in reality family caregivers may not be able to meet PAC needs as is often the hope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies explored the rising cost of PAC and its impact on overall healthcare spending, quality of care, and outcomes . Few studies have explored what hospitalized patients would like to know to make informed decisions about their PAC placement including information on the upfront financial cost of services as well as insurance coverage . Patient‐physician communication on out‐of‐pocket costs may occur infrequently, leading some to recommend physician communication with patients about out‐of‐pocket costs as an important but neglected aspect of clinical practice .…”
Section: Discussionmentioning
confidence: 99%